2022
DOI: 10.3390/ijerph192215165
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Components, and Efficacy of Telerehabilitation Approaches for People with Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is at the top of the list of non-communicable diseases with related rehabilitation needs. Digital medicine may provide continuative integrated intervention, overcoming accessibility and cost barriers. Methods: We systematically searched for randomized controlled trials on telerehabilitation (TR) in people with COPD to profile the adopted TR strategies, focusing on TR models and the main rehabilitation actions: monitoring and assessment, decision, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“… 70 The question whether pulmonary rehabilitation delivered using communication technologies is effective and safe has also been addressed by another Cochrane Review, 71 which showed that primary or maintenance pulmonary rehabilitation delivered via telerehabilitation were similarly and favorably effective with regard to outcomes such as exercise capacity, dyspnea, and HRQoL when compared with traditional, center-based, in-person pulmonary rehabilitation without compromising safety and with the likelihood of also reducing hospitalizations and anxiety. 71 Subsequent SRs demonstrated telerehabilitation as an effective strategy in COPD for maintaining and improving functioning, dyspnea and HRQoL 72 as well as with favorable effects on anxiety and depression. 73 The designs of pulmonary telerehabilitation programs were heterogeneous; however, consistently including exercise and education.…”
Section: Resultsmentioning
confidence: 99%
“… 70 The question whether pulmonary rehabilitation delivered using communication technologies is effective and safe has also been addressed by another Cochrane Review, 71 which showed that primary or maintenance pulmonary rehabilitation delivered via telerehabilitation were similarly and favorably effective with regard to outcomes such as exercise capacity, dyspnea, and HRQoL when compared with traditional, center-based, in-person pulmonary rehabilitation without compromising safety and with the likelihood of also reducing hospitalizations and anxiety. 71 Subsequent SRs demonstrated telerehabilitation as an effective strategy in COPD for maintaining and improving functioning, dyspnea and HRQoL 72 as well as with favorable effects on anxiety and depression. 73 The designs of pulmonary telerehabilitation programs were heterogeneous; however, consistently including exercise and education.…”
Section: Resultsmentioning
confidence: 99%
“…Home-based PR for COPD has been shown to be as effective as center-based PR in improving functional exercise capacity and quality of life ( 53 ), and patients with chronic respiratory disease achieved similar effectiveness and safety outcomes to center-based PR as they did with telerehabilitation ( 53 ). COPD telerehabilitation may even be able to increase and maintain the persisting benefits of PR ( 54 ).…”
Section: Remote Patient Monitoring and Wearables In Copd: Additional ...mentioning
confidence: 99%
“…Furthermore, considering the current social, epidemiological, demographic, and cultural context characterized by an increased demand for healthcare services and delivery, all National Healthcare Services (NHSs) are inclined to act to ensure economic sustainability and affordability. In particular, chronic conditions, which represent the main cause of 70% of worldwide deaths, define the relevant consumption of services and resources in all healthcare systems, considering their long-lasting nature and the severe correlated healthcare consequences [8].…”
Section: Introductionmentioning
confidence: 99%